Understanding Microbial Biofilms - Monteiro, Douglas Roberto [UNESP]; Shukla, Ashutosh Kumar (Taylor & Francis, 2025)
Biofilms are extremely organized communities of microbial cells adhering to a surface in an aqueous medium and covered by an extracellular matrix. These communities may accumulate on various living tissues and surfaces of medical devices, leading to harm to human health and loss of medical devices. Therefore, this chapter addresses the main steps involved in the development of microbial biofilms, the forms of cellular communication within the biofilm, and the mechanisms by which biofilms escape the human host’s defense cells. The first step in the biofilm formation process is initial adhesion to a particular surface, which is also known as reversible adhesion. Subsequently, this adhesion becomes irreversible and is characterized by microbial multiplication and the onset of extracellular matrix production. This is followed by the formation of microcolonies and maturation of the biofilm and finally by the dispersal phase of part of the biofilm. The cells within the biofilm communicate with each other through a mechanism known as quorum sensing. Autoinducer-2, autoinducer peptide, and N-acyl homoserine lactones are the major quorum-sensing molecules associated with bacteria, while tyrosol and farnesol are alcohols related to cellular communication in fungal biofilms. The extracellular matrix of biofilms protects microbial cells from phagocytosis by innate immune system cells, and direct contact of macrophages with the biofilm can cause disturbances in the defense cell, contributing to the persistence and tolerance of microbial biofilms. Understanding the fundamental attributes of microbial biofilms is imperative for researchers to select optimal tools for their analysis and to use antimicrobial treatments for their management.